Universe by Mykhailo Guyda - Тарасенко, О. А.; Тарасенко, А. А. (Art and Design, 2021)
Purpose of the article is to show the particular features of the model of the universe in the genre portrait-paintings and compositions of the modern Ukrainian artist M. E. Guyda are investigated. Historico-culturalogical, comparative, iconographic and iconological methods are applied. The ideological content and the particular features of the formal solution of figurative compositions are considered in the context of the heritage of world art. The national character of the images and symbols of the house, the clan and the native land are revealed; as is the nature of the manifestation of the relationship of the earthly and the heavenly. It was found that in the center of creation in compositions of M. E. Guyda is a spiritually inspired person from the folk. The depiction of people of different ages in interaction with nature helps to convey a natural course of time. It was clarified that the European aristocratic ceremonial portrait is foundational for the Ukrainian master. Artistic-stylistic analysis revealed that in the portrait-paintings "At the Well" (2013) and "Baba Kilyna" (2016), canonical composition was transformed by the artist through the expansion of space filled with individual symbolic content. The components of the ritual ceremonial portrait (columns, draperies, table-altar) are transformed into the image of a Cossack courtyard with a hedge, a tree of life, a well, a rainbow path. In the painting "Green Festivities" (2004), the house is shown as a temple. In the composition "Chumatsky Way" (2014), the world is presented as a universe – a model of the universe-house, with the architectonics of earth and sky. Scientific novelty is that the transformation of the canonical composition of the ceremonial portrait in the work of the contemporary artist M. E. Guyda is shown. The cultural and historical content of the master’s compositions was studied in connection with the problems of national self-identification and polystylism of the art of the twentieth century.is that the appeal to archetypes and symbols allowed the artist to expand the chamber space of his native Cossack house-yard to the "Model of Guyda’s Universe". The persuasiveness of individual pictorial images and symbols is based on the unity of personal, emotional perception of life with supra-individual mythological thinking. Practical significance. The presented materials, their artistic and stylistic analysis and generalization can be used in scientific research devoted to the art of portrait painting in Ukraine and in the world.